2019
DOI: 10.3389/fmicb.2019.01214
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Archaeal Holliday Junction Resolvase Hjc Inhibits Its Catalytic Activity and Facilitates DNA Repair in Sulfolobus islandicus REY15A

Abstract: Protein phosphorylation is one of the main protein post-translational modifications and regulates DNA repair in eukaryotes. Archaeal genomes encode eukaryotic-like DNA repair proteins and protein kinases (ePKs), and several proteins involved in homologous recombination repair (HRR) including Hjc, a conserved Holliday junction (HJ) resolvase in Archaea, undergo phosphorylation, indicating that phosphorylation plays important roles in HRR. Herein, we performed phosphorylation analysis of Hjc by various ePKs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
(83 reference statements)
1
10
0
1
Order By: Relevance
“…The resultant newly formed junctions can have significant impacts on genomic integrity and Holliday junction resolution is likely an important point of regulation for HR-DSBR. The cleavage activity of Hjc is repressed by phosphorylation in Sulfolobus islandicus, which is consistent with bacterial and eukaryotic resolvases [59,60]; cells are more resistant to high doses of DNA damaging agents when the phosphomimetic version of Hjc is expressed [61].…”
Section: Homologous Recombination (Hr)-dsb Repairsupporting
confidence: 71%
“…The resultant newly formed junctions can have significant impacts on genomic integrity and Holliday junction resolution is likely an important point of regulation for HR-DSBR. The cleavage activity of Hjc is repressed by phosphorylation in Sulfolobus islandicus, which is consistent with bacterial and eukaryotic resolvases [59,60]; cells are more resistant to high doses of DNA damaging agents when the phosphomimetic version of Hjc is expressed [61].…”
Section: Homologous Recombination (Hr)-dsb Repairsupporting
confidence: 71%
“…Assay of the sensitivity of strains to UV irradiation on plates was performed as described previously ( Huang et al, 2019 ). For UV-treatment of cells in liquid medium, a 30 mL aliquot at an OD 600 ∼ 0.2–0.3 was transferred to a petri dish (9 cm in diameter).…”
Section: Methodsmentioning
confidence: 99%
“…Although archaeal Rios was suggested to have a conserved role in ribosome biogenesis ( Knuppel et al, 2018 ), their function has not been established thus far. Our previous study revealed that Rio1 phosphorylated the Holliday junction resolvase Hjc in S. islandicus and regulated its nuclease activity ( Huang et al, 2019 ). However, it remains unclear what other role(s) archaeal Rio1 plays in DNA damage-induced regulatory networks.…”
Section: Introductionmentioning
confidence: 99%
“…In S. islandicus , Hjc is regulated by phosphorylation, which acts to inhibit its catalytic activity [ 433 ]. Interestingly, Hjc phosphomimetic mutants of S. islandicus exhibit increased resistance to DNA damaging agents, suggesting that phosphorylation acts to redirect repair to avoid HR that is dependent on Hjc [ 433 ].…”
Section: Dna Replicationmentioning
confidence: 99%
“…In S. islandicus , Hjc is regulated by phosphorylation, which acts to inhibit its catalytic activity [ 433 ]. Interestingly, Hjc phosphomimetic mutants of S. islandicus exhibit increased resistance to DNA damaging agents, suggesting that phosphorylation acts to redirect repair to avoid HR that is dependent on Hjc [ 433 ]. While the serine residues targeted for phosphorylation in S. islandicus Hjc are not conserved in other archaeal species, modification of Hjc and other HR proteins by phosphorylation in S. acidocaldarius is well documented [ 434 ] .…”
Section: Dna Replicationmentioning
confidence: 99%